Repetición-imitación y afasia: bases neurales y tratamiento - De Torres García, Irene (UMA Editorial, 2017)
In the past two decades, single-case studies evaluated the effect of massed repetition training to improve speech production and short-term memory deficits in conduction aphasia (CA). Improvements were reported in treated language and memory domains with modest generalisation of gains to spontaneous speech or auditory comprehension. Although these results are encouraging, sentence repetition training has not been compared with distributed speech-language therapy, and no studies have examined the role of pharmacological interventions to enhance gains promoted by these behavioural interventions in CA. To explore repetition and imitation in the context of neural basis and treatment of aphasia, we developed three studies (STUDY 1, 2 & 3). Study 1: The effects of massed sentence repetition therapy (MSRT) were compared to those of distributed speech-language therapy (DSLT) in measures of verbal output, short-term memory and repetition in patients with chronic post-stroke CA receiving treatment with the cholinesterase inhibitor donepezil (DP). Both interventions improved performance in speech production tasks, but better improvements were found with DP-MSRT than with DP-DSLT. Larger treatment effects were found for DP-MSRT in comparison with baselines and DP-DSLT in repetition of word pairs and triplets, and novel and experimental sentences with generalisation of gains to aphasia severity, connected speech and non-treated control sentences.
Repetition-imitation and aphasia: Neural Basis and treatment
Study 2: a single-case study was developed. Repetition performance was widely assessed in a patient with crossed conduction aphasia and striatal/capsular vascular lesions encompassing the right arcuate fasciculus (AF) and inferior frontal-occipital fasciculus (IFOF), the temporal stem and the white matter underneath the supramarginal gyrus. He showed lexicality effects repeating better words than non-words, but manipulation of other lexical-semantic variables exerted less influence on repetition performance. Imageability and frequency effects, production of meaning-based paraphrases during sentence repetition, or better performance on repeating novel sentences than overlearned clichés were hardly ever observed in this patient. Diffusion tensor imaging disclosed damage to the right long direct segment of the AF and IFOF with relative sparing of the anterior indirect and posterior segments of the AF, together with fully developed left perisylvian white matter pathways. These findings suggest that striatal/capsular lesions extending into the right AF and IFOF in some individuals with right hemisphere language dominance are associated with atypical repetition patterns which might reflect reduced interactions between phonological and lexical-semantic processes. Study 3: A within-patient design, with multiple assessments, was developed with the same patient as in Study 2A. The initial dose of Donepezil (5 mg/day) was titulated up to 10 mg/day and administered alone (without aphasia therapy) during 3 months (Endpoint 1). Then, the drug was combined with a verbal repetition-imitation therapy (Look-Listen and Repeat - LLR) (1 hour/day) during 2 months (Endpoint 2). Language evaluations, diffusion tensor imaging (DTI) and voxel-based morphometry (VBM) were performed at baseline and at both endpoints. Donepezil alone and combined with LLR induced marked improvement in measures of speech production (Correct Information Units/minute during picture description, and repetition of word lists, idiomatic-novel phrases and sentences). Greater benefits were observed after combined therapy and the obtained gains in speech production remained well-above baseline scores even four months after combined therapy interruption. Longitudinal DTI showed structural plasticity in the right frontal aslant tract (FAT) with both interventions and VBM additionally revealed increased grey matter density in cortical areas connected through the FAT. Donepezil alone and combined with LLR improved speech production deficits by inducing structural plastic changes in white matter tracts and grey matter areas spared by the lesion in the injured hemisphere. Conclusions: Cholinergic modulation and intensive verbal repetition-imitation therapy improve speech production deficits in crossed conduction aphasia by inducing right hemisphere structural plasticity. Conclusions: MSRT become a simultaneous training of attention, auditory and visual input processing with the activation of different semantic fields, STM, executive processing, and language production. Treatment with donepezil has a positive effect in communication skills of CA patient. We observe a summative effect between donepezil and MSRT. The improvement associates neuroplasticity changes in neuroimaging.
Keywords: Afasia - Tesis doctorales; Rehabilitación; Donepezilo; Neuroplasticidad